APLICAÇÃO DE BIOFERTILIZANTES NA CULTURA DA SOJA PRODUZIDOS EM BIODIGESTORES ALTERNATIVOS - Vaso, Larissa; Volpato, Tulio; Côrrea, Gabriela; De Freitas, Guilherme; Rojas, Matheus; Nascimento, José (ANAIS DO ENIC, 2018)
-